2015
DOI: 10.1517/17460441.2015.1018174
|View full text |Cite
|
Sign up to set email alerts
|

The use of natural products in colorectal cancer drug discovery

Abstract: The use of NPs for the discovery of anti-cancer agents has not been fully investigated. New technologies that are currently applied for synthetic compounds may be utilized for anti-cancer drug discovery including NPs for CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 92 publications
0
13
0
Order By: Relevance
“…Numerous studies have reported the anticancer effects of herbal medicines or phytochemicals for the treatment of CRC. Herbal medicines may have improved efficacy and safety compared to other regimens as well as the potential to be used as a complementary therapy for advanced colorectal adenocarcinoma and mCRC [10][11][12]. Examples of current clinically used phytochemicals include Catharanthus alkaloids (Vinca rosea) [13] and Camptotheca (happy tree, cancer tree) [14], while others are currently in clinical trials such as curcumin, green tea and soybeans [15].…”
mentioning
confidence: 99%
“…Numerous studies have reported the anticancer effects of herbal medicines or phytochemicals for the treatment of CRC. Herbal medicines may have improved efficacy and safety compared to other regimens as well as the potential to be used as a complementary therapy for advanced colorectal adenocarcinoma and mCRC [10][11][12]. Examples of current clinically used phytochemicals include Catharanthus alkaloids (Vinca rosea) [13] and Camptotheca (happy tree, cancer tree) [14], while others are currently in clinical trials such as curcumin, green tea and soybeans [15].…”
mentioning
confidence: 99%
“…According to national cancer registry (NCR) report of Malaysia, CRC was the second most common cancer diagnosed during the year 2007 (Ariffin and Saleha, 2011;Asif et al, 2016b), which highlights the need to find new treatment strategies to manage this life threatening ailment. In the recent years extensive research has been conducted on natural products to find new drug moieties that can be used safely for the prevention and treatment of CRC (Miura et al, 2015). Present study describes the molecular mechanisms responsible for in vitro cytotoxic attributes of terpenes richfraction (F-3) towards human colon carcinoma HCT 116 cells.…”
Section: Discussionmentioning
confidence: 98%
“…Identifying strategies to fight against CRC is important, as it is an emerging health problem. It is now well documented that phytochemicals, including flavonoids, alkaloids and polysaccharides, are important in anticancer therapy ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%